Thermodynamic assessments of the novel cascade air cooling system including solar heating and desiccant cooling units. (1st November 2019) - Caliskan, Hakan; Hong, Hiki; Jang, Jin Kyung
Graphical abstract: Highlights: Experimental analysis of novel cascade air cooling system. Solar heating and desiccant cooling supported cascade air cooling system. Effects of solar irradiance on energetic, exergetic and sustainability assessments. Abstract: In this study, the novel cascade system, including solar heating and solid desiccant cooling units, is developed for air cooling process and assessed through energy, exergy and sustainability approaches. The analyses are done at 10:30:00 (morning time), 11:27:54 (late morning time), 12:25:57 (noon time), 14:51:00 (afternoon time), 17:17:06 (evening time). The cooling capacity of the cascade system reaches to maximum (9.29 kW) at the noon time. Also, the maximum thermal COP of the cascade system is 1.7 at the evening time, maximum electrically driven COP is 6.665 at the noon time, and maximum general COP is 1.343 at the evening time. Furthermore, the maximum efficiency of the solar heating unit is determined at the late morning and noon time as 49.807% and 49.732%, respectively. According to the exergy analysis; the maximum exergetic cooling capacity (0.529 kW), electrically driven exergetic COP (0.369) and general exergetic COP (0.2203) rates of the cascade system are obtained at the afternoon time; while the maximum exergetic thermal COP is calculated at the evening time as 0.846. The COPs shows that the cascade system has more performance at the noon and afternoon conditions comparing the other stages.